MODEL LATIHAN PASSING BAWAH BOLA VOLI - Jajang Nugraha; Dicky Reva Apriana Sanga Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine whether the application of the underhand passing training model in volleyball can be applied in the training process. The instrument used in this study is the basic skill test for underhand passing (Measurement Foundation Skill Passing), which is designed to measure the underhand passing skills in volleyball. This study employs a research and development method (RnD) using the Borg & Gall model, which consists of ten steps. The sample used is students who participate in extracurricular activities at State High School 1 Ciwaru. The data analysis technique of this research examines normality, homogeneity, validity, reliability, and hypothesis using SPSS. The analysis results show that there is a significant effect on the implementation of the lower passing training model on students in extracurricular activities at State High School 1 Ciwaru.